Biocontrol efficiency of microencapsulated Trichoderma harzianum coupled with organic additives against potato stem rot caused by Sclerotium rolfsii - Md. Rizvi Chowdhury; Sheikh Faruk Ahmed; Bareerah Khalid; Zannatul Ferdaous Bony; Jannatul Ferdoushi Asha; Md. Khurshed Alam Bhuiyan (Plant Stress, 2023)
Potato (Solanum tuberosum L.), world's fourth most carbohydrate supplying crop is often challenged by numerous pathogens among which Sclerotium rolfsii remains one of the most damaging during both growth and storage. As biocontrol is being preferred for their safety and sustainability, the present experiment was conducted for testing the biocontrol effectiveness of microencapsulated Trichoderma harzianum application in combination with organic additives against S. rolfsii. Five combinations (no T. harzianum+no organic additive [control]; T. harzianum+no organic additive; T. harzianum+rice husk biochar; T. harzianum+mustard oil cake; and T. harzianum+tea waste) were tested against two levels of S. rolfsii (absence [control] and presence) under a polyhouse environment. Prior to that, hyper-parasitism of T. harzianum against S. rolfsii was tested in vitro which showed 63.2% growth inhibition for the later. Polyhouse study revealed 16%, 25%, 19%, 21%, 38%, 27%, 9%, 13%, 28%, 20% and 9% average increase in plant height, branch number plant–1, leaf number plant–1, shoot dry matter, root dry matter, healthy tuber, total tuber yield, leaf greenness, net photosynthetic rate, total phenolic content and total antioxidant activity respectively with a subsequent reduction of 49% unhealthy tuber and 32% disease severity index due to T. harzianum+organic additive treatments. Disease suppression and growth recovery of S. rolfsii inoculated potato plants were found significantly better when T. harzianum was applied with organic additives compared to solitary application. The results of this study would provide useful information in strategizing T. harzianum formulation preparation for effective biocontrol of potato stem rot caused by S. rolfsii.